KESADARAN HUKUM MASYARAKAT DALAM MEMANFAATKAN MEDIA SOSIAL ( STUDI TERHADAP GENERASI Z DI KOTA MAGELANG ) - Puspandari, Rr Yunita (Hukum dan Masyarakat Madani, 2021)
Social media is a means of delivering information and electronic transactions. Social media users from all over the world, including teenagers who are in the "Z" generation category. Sometimes there are many wrong ways to attract people's attention on social media in an effort to show their existence, for example doing things that lead to bullying, or saying hate speech to certain parties, this of course can have legal consequences. The purpose of this research is to determine the level of legal awareness and steps to develop legal awareness of social media for generation "Z" in Magelang City. This research is a normative and empirical legal research, the research method used by researchers to analyze research data is a qualitative method. The result of this research is that most of the Z generation in Magelang City already have legal awareness, but there are a few who have not, for that there are efforts or steps to foster and maintain legal awareness of the Z generation that can be done by parents, teaching staff and related agencies. So, there is a need for legal education to raise legal awareness in the use of social media for generation "Z" in Magelang City.
Keywords: Generation Z; Legal awareness; Social Media